The role of dopamine in foraging decisions in social insects - Ye, Dajia; Kamhi, J. Frances; Gordon, Deborah M. (Frontiers in Insect Science, 2025)
Animals often need to make decisions about whether to confront risks, and climate change is making these decisions even more critical by increasing environmental stress. Biogenic amines are crucial for modulating behavior in all animals and may contribute to behavioral adaptations to changing environments through supporting decision-making involving risk. Our review focuses on the neuromodulator dopamine in insects because of its role in risk-related behavioral choices, particularly in the context of ant foraging activity. In ants, individual decisions contribute to the collective regulation of foraging activity. We consider the role of dopamine in the regulation of collective foraging activity to manage water loss in the desert red harvester ant, Pogonomyrmex barbatus, in the southwest US that is undergoing severe drought. We discuss dopaminergic circuitry and its involvement in decisions about foraging risk, drawing from both the vertebrate and invertebrate literature, to outline areas of future research in the role of dopamine in collective decision-making in response to changing environmental conditions.